Phylogenetics, divergence and morphology of New Zealand Eleotridae (Gobiomorphus Gill) : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Ecology at Massey University, Palmerston North, New Zealand - Atkinson, Emily (Massey University, 2006)
The genus Gobiomorphus Gill (1863) is the only representative freshwater Eleotridae in New Zealand and is comprised of seven species, of which four are diadromous. The species are endemic to New Zealand and are widespread around lowland streams and coasts (with non-diadromous species penetrating further inland). The only other Gobiomorphus species are G. coxii and G. australis, which are endemic to Australia. Eleotridae are stocky fishes of small size (up to 150 mm in length) (McDowall, 1990) and are characterised by two dorsal fins, large pectoral fins, separate thoracic pelvic fins (fused in gobies) and the absence of a lateral line (McDowall. 1990; Allen et al., 2002). Gobiomorphus has had a particularly turbulent taxonomic history in the literature, spanning approximately 150 years from Gill (1863) to the present, where many species have been synonymised with one another (particularly, most Gobiomorphus species were synonymised with G. gobioides) due the plasticity of many morphological characters. Additionally, similar morphologies have led to identification difficulties. Phenotypic plasticity can also make cladistic approaches difficult (e.g. Vrijenhoek, 1998; Orti et al., 1994), for example there has been a lot of controversy surrounding G. alpinus and its species status. Furthermore, studies of evolution using morphological characters often lack an accurate perspective on relationships and origins of fish species, in particular, little information exists on the evolutionary origins of the Gobiomorphus genus. Genetic studies have contributed to resolving problems with taxonomically difficult groups by detecting diversity between morphologically similar species (where DNA variation is often not expressed phenotypically), and examining geographical divergence within species (e.g. Vrijenhoek, 1998; Kocher et al., 1989). Thus, this thesis employed two regions of mitochondrial DNA (cytochrome b and control region) to resolve issues surrounding species identification, morphological variation, phylogenetic relationships (including divergence), origins and the evolution of diadromy within the Gobiomorphus group. Mitochondrial DNA sequences were obtained from all seven Gobiomorphus species in New Zealand, as well as from both Australian Gobiomorphus. The morphology of both G. basalis and G. breviceps in the lower North Island was also examined. The results suggested that the Australasian Gobiomorphus are a polyphyletic group, although with the exclusion of G. australis the rest of the species formed a monophyletic group. The Australian group formed a polyphyletic group basal to the New Zealand monophyletic group. Gobiomorphus hubbsi, a diadromous species was found to be a sister group to the New Zealand Gobiomorphus. Clock calibrations indicated that the New Zealand and Australian groups have been isolated for about 6-37 Myr, suggesting that the New Zealand species dispersed here (in a single event) from Australia post-Gondwana break-up. These results are discussed in terms of New Zealand's geological history. Once in New Zealand there was a series of radiations; the most recent radiation produced the non-diadromous species (G. breviceps, and a G. basalis, G. cotidianus (although not all populations are diadromous) and G. alpinus species complex). Furthermore, G. huttoni and G. gobioides (both diadromous) formed a monophyletic group that is part of the first radiation, indicating that diadromy is a primitive feature of Gobiomorphus. Mitochondrial DNA accurately distinguished between G. breviceps and G. basalis (suggesting a genetic basis to morphological variation), and coupled with morphological data, identified pectoral fin ray counts as the best quantitative character for differentiating the species. However, within species high morphological variation was observed that did not fit expected patterns of geographical divergence. Limited time periods may have obscured subtle morphological divergence between catchments. Mitochondrial DNA revealed some unique haplotypes within both catchments, whereas some catchments shared identical haplotypes. The lack of divergence between catchments may have been due in part to connections during the Pleistocene, whereas populations with unique haplotypes may have been isolated for a greater length of time. Collectively, these studies highlighted the usefulness of mitochondrial DNA for exploring; phylogenetic relationships (including divergence) and solving problems with taxonomically difficult groups, and origins of fish species. Furthermore, the use of molecular data coupled with morphological data can be used to aid in the improvement of identification of morphologically similar species.
Keywords: New Zealand; Gobiomorphus -- Classification